2022
DOI: 10.1097/fjc.0000000000001265
|View full text |Cite
|
Sign up to set email alerts
|

Activation of GPR75 Signaling Pathway Contributes to the Effect of a 20-HETE Mimetic, 5,14-HEDGE, to Prevent Hypotensive and Tachycardic Responses to Lipopolysaccharide in a Rat Model of Septic Shock

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…Reduced cardiac output in conjunction with peripheral vasodilation causes severe refractory hypotension and tissue hypoperfusion leading to multiorgan dysfunction, especially in the liver, kidney, heart, and gastrointestinal tract. Further details regarding the downstream GPR75/20-HETE signaling pathways can be found in the current study of Tunctan et al 1 and previous studies by others. 20,21…”
mentioning
confidence: 62%
See 4 more Smart Citations
“…Reduced cardiac output in conjunction with peripheral vasodilation causes severe refractory hypotension and tissue hypoperfusion leading to multiorgan dysfunction, especially in the liver, kidney, heart, and gastrointestinal tract. Further details regarding the downstream GPR75/20-HETE signaling pathways can be found in the current study of Tunctan et al 1 and previous studies by others. 20,21…”
mentioning
confidence: 62%
“…In rat aortic VSMCs, GPR75 activation was associated with Gαq/11/PKC and Src-mediated phosphorylation of the K Ca channel and enhanced the response of rat renal interlobar arteries to phenylephrine. 20,21 The present study by Tunctan et al 1 investigated whether the activation of GPR75-mediated signaling in various vascular beds is responsible for the ability of 5,14-HEDGE to prevent vascular hyporeactivity, hypotension, and tachycardia in the LPS-induced rat model of septic shock. Recent studies have shown that GPR75 is highly expressed in the brain, cerebral arterioles, and pericytes, 23,24 but very little is currently known about its expression in the aorta and other vessels throughout the rest of the body.…”
Section: Evidence That a 20-hete Mimetic Prevents Septic Shock By Act...mentioning
confidence: 87%
See 3 more Smart Citations